HUBUNGAN PERUBAHAN HARGA SATUAN TENAGA KERJA DAN MATERIAL TERHADAP BIAYA DAN KEUNTUNGAN PROYEK - Adriana Frida Tanines; Laurensius Lulu; Paulus Sianto; Gregorius Paus Usboko (CV. Indie Press Edutaste, 2025)
The implementation of construction projects often experiences obstacles that arise due to inconsistencies between what is planned and implementation in the field, one of which is changes in unit prices for labor and materials. This study only analyzes changes in unit prices for labor and materials, while equipment is not analyzed because equipment is considered a fixed cost that has been calculated previously in the early stages of project planning. This study aims to calculate how much the contribution of labor and material needs costs to costs, to find out changes in costs due to changes in unit prices for labor and materials. And to find out the changes in profits that occur due to changes in unit prices for labor and materials. The study began with the collection of initial data, namely volume, coefficient and unit price from the RAB data and calculations were carried out until changes in project costs and profits were found due to changes in unit prices. The results of this study indicate that changes in construction cause changes in costs and profits, the smaller the project costs, the greater the profits. Likewise, the greater the project costs, the smaller the profits will be.